From Agricultural Zakat to Trade Zakat: Rethinking Hydroponics within Contemporary Islamic Legal Frameworks in Indonesia - Ash Shiddiqi, Muhammad; Musa, Armiadi; Jailani, Jailani; Manan, Abdul; Chalis, M. (Al-Qadha : Jurnal Hukum Islam dan Perundang-Undangan, 2025)
This study analyzes the legal gaps in traditional zakat regulations that are not yet relevant to modern agricultural systems, such as hydroponics. The aim of study is to provide conceptual and practical contributions by reviewing the views of Islamic scholars, determining the appropriate classification of zakat, and formulating fair calculations of the nisab and haul. The approach used in this research is normative-juridical, using a literature study method. Primary legal sources include classical fiqh texts, contemporary fatwas from religious scholars, and laws and regulations related to zakat in Indonesia. Secondary legal sources include scientihic journals, books, and other relevant scientihic research findings. The data collected through this documentation ware analyzed qualitatively and descriptively by comparing the characteristics of hydroponics with the criteria for zakat in agriculture and trade. The study results indicate that hydroponic characteristics, such as a continuous harvest cycle, a focus on profit, and an intensive business model, are more relevant to be categorized as trade zakat ('urūḍ al-tijārah). The ideal zakat calculation formula is based on the nisab of 85 grams of gold with a 2.5% gold content, which must be paid after one full year of ownership (haul), at the same time providing fundamental policy implications for Baitul Mal Aceh to revise the Zakat Qanun, especially by including the trade zakat category for modern agricultural products, as well as being a reference in compiling regulations that are more adaptive to the dynamics of the contemporary agribusiness system